PENGARUH KOMPETENSI TERHADAP KINERJA KARYAWAN PT. WISESAN JAYA MAKMUR KOTA TANGERANG - Nofiar Nofiar; Maswarni Maswarni; Novia Susanti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The purpose of this study was to determine the effect of competence on employee performance at PT. Wisesan Jaya Makmur. The method used is a descriptive method with a quantitative approach. The sampling technique used is saturated sampling using a sample of 60 employees of PT. Wisesan Jaya Makmur Data analysis using validity test, reliability test, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. Based on the results of the analysis, the value of the regression equation Y = 17.603 + 0.566X1, the correlation coefficient of 0.638 means that competence and performance have a strong level of relationship. The value of determination or contribution of the influence of competence (X) on employee performance (Y) is 0.407 or 40.7% while the remaining 59.3% is influenced by other factors. Hypothesis testing is obtained by the value of t arithmetic > t table or (6.314 > 2.002), this is reinforced by the probability significancy 0.000 <0.05, thus H0 is rejected and H1 is accepted meaning that there is a partially significant effect between competence on employee performance at PT Wisesan Jaya Makmur